Sustainable Development and Water Resource Scarcity - Flynn, Ph.D., Dave (Archives of Business Research, 2014)
This paper focuses on the critical relationship between climate change and sustainable development with a focus on the availability and usage of water resources, especially in China, India, and the United States. Scores of countries are over-pumping aquifers as they struggle to satisfy their growing water needs, including each of the top three grain producers—China, India, and the United States. These three, along with a number of other countries where water tables are falling, are home to more than half the world’s peopl. Energy availability may limit the ability of countries to continue their economic advancement, made critically evident in the 2011 Japan earthquake and tsunami. Nuclear energy was considered their means of achieving development goals by reducing their need to import oil and coal. This and other nuclear disasters, e.g. Chernobyl and Three Mile Island, have threatened the availability of clean water. Alternatives such as natural gas hydraulic fracturing, coal mining, and off-shore oil drilling also threaten water resources. Recommendations will be made to achieve a sustainable world economy to prevent further climate change and to increase the efficiency of water usage.